2015
DOI: 10.1039/c5cc05111h
|View full text |Cite
|
Sign up to set email alerts
|

Reversible DNA i-motif to hairpin switching induced by copper(ii) cations

Abstract: i-Motif forming DNA sequences have previously been used for many different nanotechnological applications, but all have used changes in pH to fold the DNA. Here it is shown that Cu(ii) cations can be used to re-fold i-motifs into hairpin structures, without changing the pH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 27 publications
(41 reference statements)
0
29
0
Order By: Relevance
“…This was a similar characteristic to the duplex and hairpin structures 32 . Several studies have reported the transformation of an i-motif to a hairpin-like structure 7,33 . On the other hand, the CD spectra of c-MYC IM ( Fig.…”
Section: Structural Transformation Of Vegf Im Upon Binding Of Fismentioning
confidence: 99%
“…This was a similar characteristic to the duplex and hairpin structures 32 . Several studies have reported the transformation of an i-motif to a hairpin-like structure 7,33 . On the other hand, the CD spectra of c-MYC IM ( Fig.…”
Section: Structural Transformation Of Vegf Im Upon Binding Of Fismentioning
confidence: 99%
“…In addition to (C:H:C) + pairs, recent experimental results demonstrate that a series of metal cations (M z + ) stabilize i‐motifs in terms of (C:M:C) z + pairs, notably even at neutral pH values . In contrast to stabilizing ions like Ag + or Cu + , it was further reported that cations like Na + , Cu 2+ , and Li + destabilize the i‐motif . In this context, pronounced interactions between Cu 2+ ions and DNA were reported, which are of biological importance with regard to the fact, that cancer cells usually show elevated copper levels .…”
Section: Introductionmentioning
confidence: 99%
“…There is increasing evidence that these types of structures provide opportunities to regulate DNA metabolism in bacteria [51,[75][76][77]. The genome of the bacterium Paracoccus denitrificans PD1222 has a relatively high G + C content (∼67%) and a range of biophysical, molecular, and microbiological studies show that targeting of four-stranded structures can be controlled under cellular conditions, allowing regulation of expression of some genes [48,[78][79][80][81].…”
Section: Biochemical and Cellular Impacts Of Simple Repeat Sequences mentioning
confidence: 99%